공극 규모 반응성 운송 모델링의 연산 효율 향상을 위한 지화학 반응 대리 인공신경망 모형 개발 - 김예훈(Yehoon Kim); 김호림(Ho-rim Kim); 정희원(Heewon Jung) (자원환경지질, 2024)
Pore-scale reactive transport modeling is a powerful tool used to analyze micro-scale processes where fluid flow and geochemical reactions occur. Despite its capability to examine complex hydrological and geochemical system behavior, the high computational demands for these simulations present a significant limitation. To overcome this challenge, this study evaluated artificial neural network (ANN)-based surrogate models to replace geochemical reaction calculations, which consume the majority of computational time in reactive transport simulations. The study considered two ANN models: a combined model (CM) that simultaneously accounts for mineral dissolution/precipitation and solute adsorption reactions, and an independent model (IM) that treats these reactions independently. The performance of these models was compared using metrics, including mean squared error (MSE), coefficient of determination (R2), and mass balance errors. Results indicate that IM demonstrates superior accuracy compared to CM. This finding suggests that instead of constructing a single complex model for the entire geochemical reaction network, pore-scale geochemical reactions can be effectively replaced by combining individual neural network models trained for specific reactions. 공극 규모 반응성 운송 모델링은 유체 유동과 지화학 반응의 결합이 일어나는 마이크로미터 수준의 프로세스 분석을 수행하는 연구 기법이다. 이는 지질매체 내에서 일어나는 복잡한 물질 거동을 정밀하게 고찰할 수 있게 하는 강력한 연구 기법이지만, 매우 높은 연산 자원이 필요하다는 한계가 존재한다. 이러한 한계를 극복하기 위하여, 본 연구에서는 반응성 운송 모델링에서 대부분의 연산 자원을 소모하는 지화학 반응을 대체하는 인공신경망 기반의 대리모형을 개발하였다. 공극 규모에서는 광물의 공간적 분포에 따라 독립적 지화학 반응 연산을 수행한다는 점에 착안하여 본 연구에서는 광물의 용해/침전과 용질의 흡착 반응을 동시에 고려하는 통합모형(CM)과 독립적으로 고려하는 독립모형(IM)의 두 가지 대리모형의 정확성과 효율을 비교하였다. 평균 제곱 오차(MSE), 결정 계수(R2), 질량 균형 오차(mass balance error) 등의 지표를 통해 모형들을 비교한 결과, 통합모형은 공극 규모에서 발생하는 순차적 반응에서 성능이 저하된 반면, 독립모형은 같은 조건에서도 높은 정확도를 유지하며 복잡한 지화학 반응을 효과적으로 처리하였다. 이 결과는 지화학 반응 대리모형 구축에 있어, 복잡한 지화학 반응 네트워크를 포괄하는 단일모형을 매번 새롭게 구축할 필요 없이, 개별 지화학 반응을 학습한 신경망 모형의 합성을 통하여 공극 규모의 지화학 반응을 대체할 수 있을 것으로 기대된다.